Solvent‐Assisted [(Glycine)‐(MP‐SiO2NPs)] Aggregate for Drug Loading and Cancer Therapy. Issue 27 (17th July 2020) - Amgoth, Chander; Santhosh, Rompivalasa; Malavath, Tirupathi; Singh, Avinash; Murali, Banavoth; Tang, Guping
Abstract: Herein, the amino‐acid based glycine (Gly) solubility in different solvents (ethanol, pyridine, and n‐hexane) exhibited striking interlocking behavior with mesoporous silica nanoparticles (MP‐SiO2 NPs) has been reported and discussed in detail. The synthesis of MP‐SiO2 NPs carried out employing the modified Stober's 'Sol‐Gel' method. The yielded MP‐SiO2 NPs size ranges from ∼20–80 nm, with an average particle size of ca . 36 nm. The morphology of Gly bound with MP‐SiO2 NPs was analyzed through electron microscopic imaging (SEM, TEM), followed by characterizations (BET, PXRD, DSC, TGA, EDAX) in various solvents. Interestingly, Gly dissolved in particular solvents demonstrated remarkable binding and interlocking properties with the well‐dispersed MP‐SiO2 NPs to form a foamy surface. The developed [(Gly)‐(MPSiO2 NPs)] based aggregate is stable at room temperature (∼25 °C). Further, developed [(Gly)‐(MP‐SiO2 NPs)] aggregate used to load the anticancer drug (DOX) and it shows ∼80 % loading efficacy. Whereas, the DOX release from [(Gly)‐(MP‐SiO2 NPs)] is calculated as ∼59 % after 24 hr. The designed nanoformulation [(Gly)‐(MP‐SiO2 NPs)] aggregate along with DOX shows significant inhibition ( i. e . 74 %) on K562 (chronic myeloid leukemia) blood cancer cells. Such low‐density foamy materials are believed to be utilized in industrial and pharmaceutical applications. Abstract : The following graphical abstract/TOC corroborates the steps involved in the synthesis of aggregate between glycine residue and mesoporous SiO2 nanoparticles. The aggregate between amino‐acid/glycine residue and mesoporous SiO2 nanoparticles is bio‐safe, biocompatible, and biodegradable for mankind's usage. Simple and facile Stober's ′Sol‐Gel′ method has been followed for the synthesis of MP‐SiO2 NPs. These silica nanoparticles were interlocked with glycine residue to give an aggregate with drug loading characteristic features. However, the [(Gly)‐(MP‐SiO2 NPs)] with various dispersion solvents/medium gives different aggregate morphology. Such interlocked aggregate of [(Gly)‐(MP‐SiO2 NPs)] shows remarkable drug loading efficacy followed by the targeted release and cell inhibition through in‐vitro cell‐based studies.